The Richness of Sarcocystis Species in the Common Gull (Larus canus) and Black-Headed Gull (Larus ridibundus) from Lithuania - Juozaitytė-Ngugu, Evelina; Prakas, Petras (Parasitologia (Basel, Switzerland), 2023)
The common gull (Larus canus) and the black-headed gull (Larus ridibundus) are common waterbird species in Lithuania. Until now, the composition of Sarcocystis species in these birds was unknown. The current study aimed to identify Sarcocystis spp. by the morphological examination of sarcocysts found in the muscle tissues and by DNA sequence analysis. Between 2011 and 2019, the leg muscles of 42 common gulls and 63 black-headed gulls were tested for Sarcocystis spp. Based on the methylene blue staining of squashed muscle samples, sarcocysts were detected in six common gulls (14.3%) and in six black-headed gulls (9.5%). Under a light microscope, one type of microcyst was observed. Sarcocysts were thread-like (2860–8250 × 40–180 μm) and had a smooth and thin (0.8–1.4 μm) cyst wall, while bradyzoites were banana-shaped and 5.0–9.2 × 1.3–2.4 μm in size. The sequencing of complete ITS1 showed the presence of S. columbae, S. halieti and S. wobeseri in the common gull and S. columbae and S. halieti in the black-headed gull. The highest intraspecific genetic variability was established for S. halieti, which is characterized by a wide host range. This species is considered to be pathogenic, therefore further histopathological examination of the various organs of gulls is needed.